Eknowledge of the Community of Central Buton Regency About Health Protocols to Prevent the Transmission of Covid-19 - Risnah Fisteria; Titien Siwi Hartayu (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Since 2020 the world was shocked by the Corona Virus which is a new type of virus called SARS-CoV2 (Covid-19). This virus has infected thousands of millions of people around the world in a very short time (Dwidevi, 2020). Especially in Indonesia, the Government has issued a disaster emergency status starting from February 29, 2020 to May 29, 2020 related to the corona virus pandemic with a period of 91 days (Buana, 2020). This study aims to identify an overview of public knowledge regarding the factors in health protocols that must be adhered to in preventing Covid-19 and examine the influence of health protocols on people's lifestyles. The data in this study were collected by in-depth interviews through qualitative research methods, using open-ended questions and obtained 5 themes to facilitate the process of data analysis by researchers. It can be concluded that public knowledge in the application of health protocols in Central Buton Regency is quite good even though with different perspectives and perceptions, most people understand the importance of protecting themselves from Covid-19 transmission, but many people still have doubts about the existence of Covid -19 due to the lack of willingness of facilities to make a response to comply with health protocols. This is known from the number of respondents who know the importance of health protocols such as wearing masks as many as 83 respondents, washing hands as many as 86 respondents and 53 respondents who apply health protocols by maintaining / social distance.